Intention to patronage muslim friendly hotel among millennials in northern region of Malaysia - Nursyahindah, Azhaar (2020)
Muslim-friendly tourism is now growing rapidly and is in high demand in Malaysia, especially for tourists from the Middle East. In relation to Muslim-friendly tourism, it is recorded that Millennials among the largest number of Muslim-friendly hotel guest. Although the demand for Muslim-friendly hotels is increasing, there is still insufficient data on the factors that can influence and affect the intention to patronage Muslim-friendly hotels among Millennials in Malaysia. Therefore, this study aims to determine the important factors related to the intention to patronage Muslim-friendly hotels among Millennials in Malaysia by using Theory of Planned Behavior (TPB). The independent variables of this study comprise the attitude towards Muslim-friendly hotels, halal awareness, e-WOM, brand image and religiosity. The dependent variable is patronage intention to Muslim-friendly hotels. The quantitative research method via Google form questionnaire was used as the research instrument to collect data. A total of 335 samples were randomly selected from UUM postgraduate students. The collected data were analysed by using Statistical Packages for Social Science version 26.0 (SPSS 26.0). The reliability test, normality test, descriptive test, Pearson correlation and multiple linear regression had been employed in this study. The Pearson correlation and multiple linear regression were used to test the relationship between independent variables and dependent variables. The results revealed positive and significant influence between attitude towards Muslim-friendly hotels, halal awareness, e-WOM, brand image dan religiosity with patronage intention to Muslim-friendly hotels. Finally, the contributions for practicality and academicians and some recommendations for future research were discussed.